1976
DOI: 10.1159/000225146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pyridoxine on the Growth of Morris Hepatoma No. 7288Ctc and Enzyme Activity

Abstract: The effect(s) of lack of dietary pyridoxine (PX) on the growth of Morris hepatoma no. 7288Ctc was studied. Buffalo strain female rats were fed a diet lacking PX. Pair-fed controls were fed the same diet with PX added. Animals were inoculated with no. 7288Ctc hepatoma cells at 21 days and were sacrificed 16 days later. Host livers and tumors were removed, weights recorded and the activity of tyrosine aminotransferase (TAT; L-tyrosine: 2-oxoglutarate aminotransferase, EC 2.6.1.5) was determined in both host live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The vast majority of such early studies, most of which were performed in immunodeficient rodents, concluded that systemic vitamin B6 deficiency exerts consistent antineoplastic effects, [25][26][27][28][29] most likely as highly proliferating malignant cells are characterized by an intense metabolic activity that requires adequate levels of bioactive PLP. [30][31][32][33][34][35] These observations ignited an intense experimental effort aimed at the identification and characterization of vitamin B6 antagonists with potential antineoplastic applications. [36][37][38][39][40][41] Unfortunately, none of these agents has ever exhibited a preclinical activity profile compatible with clinical development.…”
Section: Preclinical Observationsmentioning
confidence: 99%
“…The vast majority of such early studies, most of which were performed in immunodeficient rodents, concluded that systemic vitamin B6 deficiency exerts consistent antineoplastic effects, [25][26][27][28][29] most likely as highly proliferating malignant cells are characterized by an intense metabolic activity that requires adequate levels of bioactive PLP. [30][31][32][33][34][35] These observations ignited an intense experimental effort aimed at the identification and characterization of vitamin B6 antagonists with potential antineoplastic applications. [36][37][38][39][40][41] Unfortunately, none of these agents has ever exhibited a preclinical activity profile compatible with clinical development.…”
Section: Preclinical Observationsmentioning
confidence: 99%
“…Biochemicals Corp., Cleveland. O H ) diet lacking pyridoxine [2,8,10]. A fter 21 days, cells from Morris hepatom a No.…”
Section: Methodsmentioning
confidence: 99%
“…A fter 21 days, cells from Morris hepatom a No. 7777 (gen. 101) were inoculated into the hinds legs of the animals [2,8,10]. The animals were maintained on a strict lighting schedule.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation